Human biological characteristics of fructose - Biró György (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2018)
Fructose is a natural ingredient of human nutrition, and it comes mainly from fruits and honey, and to a certain extent, from vegetables. In these sources, it is found partially in the free form of the sugar, and partially as one of the components of the disaccharide sucrose. In recent decades, the use of corn syrup, based on decomposed corn starch and containing large amounts of free fructose, and of enzymatically treated sucrose, also known as invert sugar, for the sweetening of various foods has been spreading rapidly, leading to the excessive intake of fructose. Due to the complex nature of the diet, it is very difficult to examine its consequences on the health of the consumer, transposition of the results of animal experiments to humans requires careful consideration, and is not always feasible. Despite these difficulties, it is worthwhile and important to review previous studies. There is no doubt that fructose participates in metabolism in a unique way, its behavior differs from that of glucose, which has an essential function in humans. Therefore, different physiological consequences have to be considered. Diseases of the cardiovascular system, obesity, symptoms of the metabolic syndrome, and even malig-nant tumors may be related to excessive fructose intake. Epidemiological studies and research on the correlations do not always present a consistent picture, there are differ-ing results. Resolving contradictions still requires a great amount of analysis. However, the power of science lies exactly in the fact that it can provide a clear picture through evidence and counter-arguments.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék